PENYEMBUNYIAN CIPHERTEXT ALGORITMA GOST PADA CITRA KE DALAM AUDIO DENGAN METODE LEAST SIGNIFICANT BIT - Abduh Riski; Heri Purwantoro; Ahmad Kamsyakawuni (Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
Government Standard (GOST) is a 64-bit block cipher algorithm with 32 round, use a 256-bit key. The weakness of this algorithm is the keys so simple, than make cryptanalyst easy to break this algorithm. Least Significant Bit (LSB) use to insert message into another form without changing the form of the cover after insertion. This research does by hiding encrypted ciphertext to image and hiding image into audio. This research use grayscale and RBG image with BMP and PNG format. Audio using music with wav format. Security analysis using differential analysis NPCR and UACI. Security analysis aims to calculate percentage from cover after hiding the message. The smaller the NPCR and UACI values, the higher the level of security the message is hidden. The results of the analysis of concealment in the image obtained by the average values of NPCR and UACI were 99.98% and 3.46% respectively. While the results of the analysis of hiding in audio obtained the average value of NPCR and UACI were 83.78% and 12.66% respectively.